Orally delivered biodegradable targeted inflammation resolving pectin-coated nanoparticles induce anastomotic healing post intestinal surgery - Jong Hyun Lee; Stefan Reischl; Robert Leon Walter; Vincent Vieregge; Marie-Christin Weber; Runxin Xu; Hao Chen; Kamacay Cira; Atsuko Kasajima; Helmut Friess; Philipp-Alexander Neumann; Nazila Kamaly (Scientific Reports)
Abstract Targeted perioperative therapeutics supporting anastomotic healing during colitis are an urgent medical need. This study aimed to develop and evaluate a novel nanoparticle (NP)-based drug delivery system for improving anastomotic healing in Inflammatory bowel disease (IBD) patients following surgery. We developed pectin-coated polymeric NPs encapsulating the inflammation-resolving peptide Ac2-26. These NPs are designed to survive gastric passage, facilitate localized release in the colon via microbial pectinase degradation, and bind to the intestinal wound through collagen IV targeting. We investigated these NPs in a murine surgical model combining intestinal anastomosis with preoperative colitis induction. Perioperative administration of pectin-chitosan coated NPs containing Ac2-26 (P-C-Col IV-Ac2-26-NP) reduced colitis activity postoperatively. Macroscopic wound closure improved, as evaluated by endoscopy and intraabdominal adhesion scoring. Microscopic analysis revealed an improved semiquantitative healing score in the treatment group. This proof-of-concept study demonstrates that novel P-C-Col IV-Ac2-26-NP could be a promising and clinically feasible perioperative treatment strategy for IBD patients undergoing intestinal surgery. The targeted delivery system shows potential for enhancing anastomotic healing and reducing postoperative complications in this IBD patient population.